Drought challenges in a context of soil use sustainability - Pereira, L.S. (2011)
Droughts are natural but temporary imbalances of water availability, consisting of a persistent lower-than-average precipitation, of uncertain frequency, duration and severity, of unpredictable or difficult to predict occurrence, resulting in diminished water resources availability and impacts on natural and man-made ecosystems. To successfully cope with drought there is a need to understand the characteristics and consequences of related phenomena; however, differences in the perception of drought lead to difficulties in adopting risk management. The effectiveness of drought risk management depends upon drought monitoring, drought prediction and warning capabilities, and means to provide information to users, as well as on related awareness of populations. For drought monitoring and warning, drought indices are useful. The SPI has been extensively used in Portugal and stochastic methods have been developed for prediction of drought class transitions to be used for early warning. For agricultural purposes, the PDSI was modified and successfully referred to the rainfed olive crop, thus originating the MedPDSI. Its evaluation against the SPI and PDSI shows the appropriateness of this index. Relative to information systems, a variety of approaches were used to support deficit irrigation. However, its economic feasibility is questionable and more studies are required to assess ways to improve irrigation under drought